Relationships Among Perceived Functional Capacity, Self‐Efficacy, and Disability After Dysvascular Amputation. Issue 10 (24th March 2018) - Miller, Matthew J.; Magnusson, Dawn M.; Lev, Guy; Fields, Thomas T.; Cook, Paul F.; Stevens‐Lapsley, Jennifer E.; Christiansen, Cory L.
Abstract: Background: Prosthesis rehabilitation after dysvascular transtibial amputation (TTA) is focused on optimizing functional capacity with limited emphasis on promoting health self‐efficacy. Self‐efficacy interventions decrease disability for people living with chronic disease, but the influence of self‐efficacy on disability is unknown for people with dysvascular TTA. Objectives: To identify if self‐efficacy mediates the relationship between self‐reported functional capacity and disability after dysvascular TTA. Design: Cross‐sectional, secondary data analysis. Setting: Outpatient rehabilitation facilities. Participants: Thirty‐eight men (63.6 ± 9.1 years old) with dysvascular TTA. Methods: Participants had been living with an amputation for less than 6 months and using walking as their primary form of locomotion using a prosthesis. The independent variable, functional capacity, was measured using the Prosthesis Evaluation Questionnaire–Mobility Scale (PEQ‐MS). The proposed mediator, self‐efficacy, was measured with the Self‐Efficacy of Managing Chronic Disease questionnaire (SEMCD). Main Outcome Measure: Disability was measured using the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) questionnaire. Results: The relationship between self‐reported functional capacity and disability is partially mediated by self‐efficacy. Relationships between WHODAS 2.0 and PEQ‐MS ( r = –0.61), WHODAS 2.0 and SEMCD ( r = –0.51), and PEQ‐MS and SEMCD ( r = 0.44) were significant ( P < .01). Controlling for SEMCD ( P = .04), the relationship between PEQ‐MS and WHODAS 2.0 remained significant ( P < .01). Statistically significant mediation was determined by a bootstrap method for the product of coefficients (95% confidence interval: –2.23, –7.39). Conclusions: This study provides initial evidence that the relationship between self‐reported functional capacity and disability is partially mediated by self‐efficacy after dysvascular TTA. The longitudinal effect of self‐efficacy should be further examined to identify causal pathways of disability after dysvascular amputation. Furthermore, additional factors contributing to the relationship between self‐reported functional capacity and disability need to be identified. Level of Evidence: III